2021
DOI: 10.3390/polym13081182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Degradation Study of Polyhedral Oligomeric Silsesquioxane (POSS) Modified Phenolic Resin

Abstract: In this paper, a new polyhedral oligomeric silsesquioxane containing a phenol group (POSS-Phenol) is prepared through the Michael addition reaction, which is added to the synthesis of phenolic resin as a functional monomer. Infrared spectroscopy (IR) is used to demonstrate the chemistry structure of the synthesized POSS modified phenolic resin. After introducing POSS into the resole, a comprehensive study is conducted to reveal the effects of POSS on the thermal degradation of phenolic resin. First, thermal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The intensity of the (002) peak decreased after being composited with PF, which could be attributed to the decreased degree of crystallinity [ 15 ]. The broad peaks at about 19.1° could be related to the crystallized carbon chain in the PF polymer [ 16 ], which is consistent with the TEM analysis.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The intensity of the (002) peak decreased after being composited with PF, which could be attributed to the decreased degree of crystallinity [ 15 ]. The broad peaks at about 19.1° could be related to the crystallized carbon chain in the PF polymer [ 16 ], which is consistent with the TEM analysis.…”
Section: Resultssupporting
confidence: 73%
“…The peaks at about 1600 and 1450 cm −1 are assigned to the C=C vibration [ 17 ]. The absorption peaks at about 1015 and 1250 cm −1 are assigned to the C-O vibration of aliphatic groups and methylol aromatic groups, respectively [ 16 ]. The peaks at about 3400 cm −1 might be assigned to the -OH groups of PF and BN-OH [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among silsesquioxanes, polyhedral oligomeric silsesquioxane (POSS) is a well-defined nanosized cage molecule consisting of a rigid silica framework symmetrically surrounded by eight organic groups. , POSS has attracted attention as a building block for the preparation of organic–inorganic hybrid materials because it offers a combination of inorganic and organic properties. For example, in Si 8 O 12 , the rigid silica framework exhibits enhanced thermal and mechanical properties, and the eight organic groups render it compatible or reactive toward organic molecules. Furthermore, POSS exhibits enhanced material properties as a nanofiller, and its derivatives have been applied to the building blocks of nanostructures and the biomedical and energy-related materials. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a special class of amphiphiles, which is called giant surfactants or giant amphiphiles, has drawn considerable attention. Compared with soft-chain segments of traditional amphiphilic polymers, these giant surfactants show a hybrid molecular structure and contain molecular nanoparticles, such as functional polyhedral oligomeric silsesquioxane (POSS), fullerene (C 60 ), polyoxometalates, and so forth, have three-dimensional rigid nanostructures and can be modified with different peripheral groups, and hence the corresponding giant surfactants have a more precisely controlled molecular structure. , Due to chemical incompatibility and geometric structural asymmetry, giant surfactants produce various structures through the assembly process. For instance, Yu et al synthesized a giant surfactant composed of a carboxylic acid-functionalized POSS with a polystyrene tail that can self-organize into spherical, cylindrical, and vesicular micelles in selective solvents . Yue et al reported Frank–Kasper and quasicrystal phases of giant surfactants by tuning the flexible polymer tail number and tail length .…”
Section: Introductionmentioning
confidence: 99%